МОНИТОРИНГ ПО УМЕНЬШЕНИЮ РАДИОЭКОЛОГИЧЕСКОГО ВЛИЯНИЯ НА ОКРУЖАЮЩУЮ СРЕДУ - Тимофеева, С.С.; Мусаев, М.Н. (SCIENCE and SOCIETY, 2021)
The purpose of professional radiation monitoring is to protect personnel and the environment from the harmful effects of ionizing radiation and to establish a normative annual limit of the annual effective dose. This is usually achieved by conducting continuous monitoring or surveys of production areas.
Keywords: monitoring; ecology; soil; risk; environment